Selective Biodetection Platform for Melanoma Diagnosis Using Functionalized THz Metamaterials - Richter, Merle; Loth, Yannik; Wigger, Anna K.; Rachinger, Nicole; Nordhoff, Daniela; Stock, Daniel; Boßerhoff, Anja Katrin; Bolivar, Peter Haring (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2023)
In this contribution, we propose a promising diagnostic platform for various biosensing tasks. More precisely, we demonstrate its capabability of selective and sensitive detection of the early growth response protein 2 (EGR2). This protein is a transcription factor, which is found in increased activities in melanoma cells. The analysis was performed with the proposed THz biosensor on a complex sample of nucleus proteins. Categorically, the sensor belongs to the frequency selective surface type metamaterials and is composed of an array unit cells, each containing an asymmetric double split ring resonator. The single resonator elements are slits in a metallic layer and are enhanced by an undercut etch. This enables the active area of the sensor to be functionalized selectively. On one sensor chip, multiple query fields containing the metamaterial array are located, thereby enabling internal referencing and multiple analyses to take place in one measurement sequence.
CRIS-Team Scopus Importer:2023-12-08